'Careful living': Frederick Douglass's phenomenology of embodied experience. Issue 10 (26th November 2019) - Lewis, Jennifer
ABSTRACT: In My Bondage and My Freedom Douglass wrote that, among the abolitionists, he 'forg[o]t' that his 'skin was dark' and his 'hair crisped'. Few critics have paid much attention to this statement and those who have, have tended to read it figuratively. In this article, I draw on the work of Merleau-Ponty, Fanon, and Leder to develop a phenomenological reading that attends to descriptions of lived experience and therefore takes this statement literally, as a revelatory expression of racial embodiment. I argue that it forms part of Douglass's analysis of how black men and women were made to experience their 'dark' skin in nineteenth century America, how this forced them into what he calls 'careful living', and how an alternative, resisting embodied persona might be expressed. Finally, I argue that reading phenomenologically, through the embodied experiences authors like Douglass describe, enables a shift in criticism, towards readings that fully attend to the complexity of lived experience.